Treatment of photojournalism in reference stories of photography - Domenech Fabregat, Hugo (2022)
Photojournalism theorists warn of the need to know the history of this field to achieve their practical and analytical domain. However, most of the stories of photojournalism appear included only as a brief chapter on the general discipline manuals. This paper presents an analysis of these manuals in order to signify their expository lines and structuring criteria, but also to report the most significant absences that affect the histories of photojournalism raised so far. The results point to evaluate most of the histories analyzed as deficient in relation to the study of social, technological and cultural context of the selected images.